Macromolecule Synthesis in Temperature-sensitive Mutants of Yeast - Hartwell, Leland H. (1967)
Approximately 400 temperature-sensitive mutants of Saccharomyces cerevisiae were isolated. The mutants were unable to form colonies on enriched media at 36 C, but grew normally, or nearly so, at 23 C. The mutants were tested for loss of viability, change in morphology, increase in cell number, and the ability to synthesize protein, ribonucleic acid (RNA), and deoxyribonucleic acid (DNA) after a shift from 23 to 36 C. Mutations were found which resulted in a preferential loss of ability to carry out protein synthesis, RNA synthesis, DNA synthesis, cell division, or cell-wall formation. Diploid cells heterozygous for the temperature-sensitive mutations were constructed and tested for their ability to form colonies at 36 C. Four mutations dominant to their wild-type allele were identified.